Higher education in India : in search of quality - Panda, Santosh K. (Santosh Kumar), 1959-; Powar, K. B.; Association of Indian Universities (New Delhi : Association of Indian Universities, 1995)
Contributed articles
Includes bibliographical references
Keywords: Education, Higher -- India; Higher education and state -- India